Effects of Thoracic Paravertebral Blockon Inflammatory Response, Stress Response, Hemodynamics and Anesthesia Resuscitation inGallbladder Carcinoma - Liu, Dunhua; Liu, Haiyan; Wu, Jun; Gong, Bing (Cellular and Molecular Biology, 2022)
The study aimed to explore the effects of the ultrasound-guided thoracic paravertebral block (TPVB) on the inflammatory response, stress response, hemodynamics and anesthesia resuscitation in gallbladder carcinoma. Eighty gallbladder carcinoma patients undergoing open cholecystectomy in Heilongjiang Provincial Hospital from February 2016 to April 2019 were selected and divided into observation group (n=40) and control group (n=40) using a random number table. All patients underwent open cholecystectomy under general anesthesia and tracheal intubation. Patient-controlled intravenous analgesia was adopted after the operation in the control group, while right TPVB was performed before general anesthesia in the observation group. The changes in inflammatory factors and oxidative stress factors were compared between the two groups, the anesthesia resuscitation indexes, and the changes in the bispectral index (BIS) and Ramsay score during anesthesia resuscitation were recorded, and the changes in the hemodynamic indexes in perianesthesia and anesthesia resuscitation-related complications were analyzed. At 15 min after anesthesia, the observation group had lower levels of inflammatory factors high-sensitivity C-reactive protein (hs-CRP) and interleukin-6 (IL-6) (p<0.05), malondialdehyde (MDA) (p<0.05) and a higher level of superoxide dismutase (SOD) (p<0.05) than the control group. The anesthesia resuscitation time was shorter in the observation group than that in the control group (p<0.05). At 10 min, 20 min and 30 min after anesthesia, both BIS and Ramsay scores were significantly higher in the observation group than those in the control group (p<0.05). Moreover, the proportion of circulatory function-related complications and anesthesia resuscitation-related complications were lower in the observation group than that in the control group (p<0.05). The NRS score in the observation group was lower than that in the control group after anesthesia (p<0.05). TPVB in perianesthesia for gallbladder carcinoma patients can effectively lower the body’s inflammatory and stress responses, promote anesthesia resuscitation, reduce complications in perianesthesia, and relieve postoperative pain.